Characterization of robotized CMT-WAAM carbon steel. (December 2022) - Tankova, Trayana; Andrade, David; Branco, Ricardo; Zhu, Carlos; Rodrigues, Dulce; Simões da Silva, Luís
Abstract: This paper analyses the microstructural and mechanical properties of carbon steel coupons produced by CMT-WAAM. The strategy adopted in the fabrication of the test specimens using a robotised facility is explained. Then, the results of the mechanical characterization performed using as-built and machined samples, extracted in several directions (0°, 45°, 90°) relative to the material deposition trajectory, are analysed. The yield and ultimate tensile strengths were determined by performing tensile tests and the Young's modulus was determined using ultra-micro hardness measurements. A deep microstructural characterization was also performed by optical microscopy for establishing a direct relationship between the manufacturing procedures and the registered mechanical properties. The failure micro-mechanisms associated with the building orientation and the surface condition was also examined by scanning electron microscopy. It was found out that the additive manufactured material has isotropic tensile properties, which result from the formation of an annealed microstructure upon cooling from the successive CMT-WAAM thermal cycles. The machined specimens exhibit higher strength and ductility than the as-built ones. The fracture surfaces of both machined and as-built coupons showed ductile failure. The results of the uniaxial tensile tests indicate that the machined and as-built WAAM steel walls satisfy the requirements of a structural steel grade as specified by Eurocode 3. Highlights: Mechanical characterization of CMT-WAAM carbon steel in different directions with respect to the build direction. Characterization of as built and machined specimens. Microstructural analyses and hardness study of CMT-WAAM carbon steel. Analyses of the fracture surfaces by SEM.